Pengaruh Transformasi Organisasi Terhadap Kinerja Dengan Motivasi Dan Kompensasi Sebagai Variabel Mediasi Pada Personil Project Management Office PT Perusahaan Gas Negara Tbk - Armynas Handyas Wijayatma; Liswandi Liswandi; Sugilar Sugilar (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
The main objective of this study is to examine and analyze the effect of organizational transformation on performance with motivation and compensation as mediating variables in the project management office (“PMO”) personnel of PT Perusahaan Gas Negara Tbk. (“PGN”) by using a quantitative descriptive approach. The data in this study were obtained from PMO organic employees who work at PGN. The total population of PMO organic employees at the time the research was conducted was 118 (one hundred and eighteen) people. While the samples taken in this study were organic employees with positions ranging from 'Staff' to 'Vice President'. The data analysis in this study used an alternative method of structural equation modeling (SEM), namely partial least squares (PLS). The first stage in this research is to test the validity of each variable's statement indicator along with their reliability. The second stage examines the relationship between the existing hypotheses for both direct effects and indirect effects between research variables. The results of this study indicate that PGN’s organizational transformation has a significant effect on PMO employee performance, either through motivation or compensation as mediation or without the mediation.